Pendampingan Program Hidup Bersih di Lembaga Masyarakat Desa Hutan Wono Sedyo Mulyo - Tri Vita Yuliasih; Wahilal Fikri Zein; Muhammad Nur Rohman; Mutia; Heri Sujianto (Jurnal Abdikarya Pembangunan, 2022)
Residents of Krandegan Village who joined LMDH Wono Sedyo Mulyo have an important role in the preservation of the surrounding forest. The ability to carry out self-preservation activities needs to be improved by adding knowledge of Islamic teachings on hygiene which includes physical and mental hygiene. The assistance uses Participated Action research which emphasizes the cooperation between the Service Team and the Management and Members of LMDH. The activity is divided into four stages. The first stage of the implementation of the delivery of hygiene materials is based on the perspective of the Qur'an. The second phase of the submission of cooperation with the Ngawi Environmental Agency and the Ngrambe Sub-district Health Center. The third phase is the implementation of cooperation with the Ngrambe Health Center in assisting the cleaning of water places in residents' homes and the distribution of Abate. The Strengthening Stage of field practice by carrying out training on organic and inorganic waste management. Greening by planting Tabebuya along the village road and planting family medicinal plants in the Krandegan village office. The benefits of activities for members include increasing knowledge about clean living behaviors based on the teachings of the Qur'an, namely QS Al-Baqarah verses 6, 11, 151, and QS At-Taubah verse 80. Skills in processing household waste by making organic fertilizers and crafting from the results of household waste sorting. The benefit of the institution is the establishment of cooperation with related agencies that can support the LMDH hygiene activity program. Meanwhile, the benefits for the village in the long term can improve the air quality and beauty of the village due to the planting of Tabebuya and TOGA Warga Desa krandegan yang bergabung dalam LMDH Wono Sedyo Mulyo memiliki peran penting dalam pelestarian hutan di sekitarnya. Kemampuan dalam kegiatan pelestarian mandiri perlu ditingkatkan dengan penambahan pengetahuan ajaran Islam tentang kebersihan yang mencakup kebersihan fisik dan batin. Pendampingan menggunakan Participated Action research yang menekankan kerjasama antara Tim Pengabdi dengan Pengurus dan Anggota LMDH.Kegiatan dibagi menjadi empat tahap. Tahap pertama pelaksanaan penyampaian materi kebersihan berdasarkan perspektif Al-Qur’an. Tahap Kedua pengajuan kerjasama dengan Dinas Lingkungan Hidup Ngawi dan Puskesmas Kecamatan Ngrambe.Tahap ketiga, pelaksanaan kerjasama dengan Puskesmas Ngrambe dalam kegiatan pendampingan pembersihan tempat air di rumah warga dan pembagian Abate. Tahap Keeampat praktik lapangan dengan melaksanakan pelatihan pengelolaan sampah organik dan anorganik. Penghijauan dengan menanam Tabebuya di sepanjang jalan desa dan penanaman tanaman obat keluarga di kantor desa Krandegan. Manfaat kegiatan pada anggota meliputi bertambahnya pengetahuan tentang perilaku hidup bersih berdasarkan ajaran Al-Qur’an, yaitu QS Al-Baqarah ayat 6, 11, 151 dan QS At-Taubah ayat 80. Ketrampilan dalam melakukan pengolahan sampah rumah tangga dengan melakukan pembuatan pupuk organik dan prakarya dari hasil pemilahan sampah rumah tangga. Manfaat pada lembaga adalah terjalinnya kerjasama dengan pihak dinas terkait yang dapat menunjang program kegiatan kebersihan LMDH. Sedangkan manfaat bagi desa dalam jangka panjang mampu meningkatan kualitas udara dan keindahan desa karena penanaman Tabebuya dan TOGA.